Retinal Prostheses and Artificial Vision - Emin Özmert; Umut Arslan (Türk Oftalmoloji Dergisi, 2019)

(untitled)
In outer retinal degenerative diseases such as retinitis pigmentosa, choroideremia, and geographic atrophy, 30% of the ganglion cell layer in the macula remains intact. With subretinal and epiretinal prostheses, these inner retinal cells are stimulated with controlled electrical current by either a microphotodiode placed in the subretinal area or a microelectrode array tacked to the epiretinal region. As the patient learns to interpret the resulting phosphene patterns created in the brain through special rehabilitation exercises, their orientation, mobility, and quality of life increase. Implants that stimulate the lateral geniculate nucleus or visual cortex are currently being studied for diseases in which the ganglion cells and optic nerve are completely destroyed.